Legal regulation of the principle of transparency in the budgetary process of the Republic of Poland - Yankevich, Semen (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
The article describes the organizational and legal foundation of the principle of budget transparency in Poland. The study considers the legal basis for access to information about the activities of public authorities and the legal foundation of the principle of transparency of the budgetary process in the Republic of Poland. The main instruments for achievement of transparency of all operations with public funds such as budget classification, the cash servicing of budget implementation, budget accounting and reporting are analysed. While attempting to describe the aforementioned matters, the author proposes a definition of the term “budget transparency”.